Artemisinin and derivatives in the treatment of uncomplicated malaria. - White, N; Olliaro, P (1998)
Artemisinin and its derivatives are the most rapidly acting antimalarials known to-date and are well-tolerated. All derivatives in use today are produced by semi-synthesis from artemisinin: dihydroartemisinin is the product of the first step; more synthetic steps give rise to artesunate, artemether and arteether which are metabolised back to dihydroartemisinin in the body. Although their residence in the body after oral administration is very short (with half-lives of < 2 hours), they can be administered once daily. By acting on ring stages, they clear peripheral parasitaemia more quickly than other antimalarial drugs and prevent the development into mature sequestering blood stages. They are effective against all human malaria parasites, notably multidrug-resistant Plasmodium falciparum. They have anti-transmission properties, too. So far, resistance to this class of compounds has not been reported. However, when used alone, they require long treatment courses (7 days). So, combination with long-half life drugs such as mefloquine appears to be the best approach to mutually protect both drugs against resistance. While reported in experimental animals, there is no evidence neurotoxicity in human beings. Whether such event could occur after continuous or discontinuous use is not clear.